Case Report: Nintedanib for Pembrolizumab-Related Pneumonitis in a Patient With Non-Small Cell Lung Cancer - Xie, Xiao-Hong; Deng, Hai-Yi; Lin, Xin-Qing; Wu, Jian-Hui; Liu, Ming; Xie, Zhan-Hong; Qin, Yin-Yin; Zhou, Cheng-Zhi (Frontiers in Oncology, 2021)
Pembrolizumab, an immune checkpoint inhibitor (ICI) approved for advanced non-small cell lung cancer (NSCLC) treatment, has shown superior survival benefits. However, pembrolizumab may lead to severe immune-related adverse events (irAEs), such as checkpoint inhibitor-related pneumonitis (CIP). The routine treatment of CIP was based on systemic corticosteroids, but the therapies are limited for patients who are unsuitable for steroid therapy. Here, we present the first successful treatment of nintedanib for pembrolizumab-related pneumonitis in a patient with advanced NSCLC.